Perancangan Sistem Produksi Ekstrak Lemon dengan Discrete Event Simulation - Syabira, Zahrayna Shebina; Pulungan, Muhammad Almaududi; Prambudia, Yudha (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
XYZ Company is a Micro, Small, and Medium Enterprise (MSME) that is engaged in the production of fruit juice drinks with the type of production produced being lemon extract. Unfulfilled demand for lemon extract products is the main problem faced by XYZ Company. This study aims to optimize the production system and provide suggestions for improvements to increase production capacity to achieve production targets using discrete event simulation. Production target planning is determined using demand forecasting. The results of model simulations that have been verified and validated show that the existing production system cannot achieve production targets. This problem is caused by the production process still using manual tools. The experimental design was carried out in the washing, cutting, squeezing, and packaging processes. Of the total of 9 alternative scenarios compared, it is known that alternative scenario C has the best results for achieving production targets with an increase in company output of 15,5% compared to the initial model.Keywords - Demand Forecasting, Discrete Event Simulation, Lemon Extract.